(untitled) (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2025)
Since 2011, scouting activities at MI Ma’arif Sraten in Semarang Regency have not been conducted regularly. Activities only appeared during the Pesta Siaga competition for selected students, and during the COVID-19 pandemic they stopped completely. Consequently, students lost a platform to develop discipline, leadership, teamwork, and independence. This program aimed to: (1) revive scouting activities at MI Ma’arif Sraten, (2) equip students in grades 4–6 with basic scouting skills, and (3) integrate Islamic values into scouting. The method was implemented through a Friday–Saturday Camp (Perjusa) on August 8–9, 2025, involving 50 students guided by nine teachers. Activities emphasized hands-on practice, including tent setup, ceremony drills, marching, code breaking, cheers, wide games, and a campfire. All sessions were combined with Islamic practices such as congregational prayers, memorization of short suras, and time management discipline. The results showed high enthusiasm; students who previously lacked experience were able to acquire and practice basic scouting skills effectively. Thus, Perjusa proved effective as a means of revitalizing scouting with Islamic values and served as a medium for character building in discipline, independence, religiosity, and social responsibility.